Pemberdayaan Kader Posyandu dan Orang Tua dalam melakukan Stimulasi, Deteksi dan Intervensi Dini Tumbuh Kembang Anak - Matje Meriaty Huru; Mamoh, Kamilus; Seran, Agustina Abuk; Kosad, Maria Florentina Nining (Universitas Merdeka Surabaya, 2025)
The growth and development of children under five is a crucial phase that affects the quality of life in the future. Early Growth and Development Stimulation, Detection, and Intervention (SDIDTK) is one of the important strategies to identify and deal with growth and development problems from an early age. The low knowledge and skills of Posyandu cadres and parents in conducting SDIDTK in East Penfui Village, Central Kupang District, Kupang Regency is one of the factors that can hinder early detection and proper handling. Therefore, empowering Posyandu cadres and parents is a strategic step to increase their capacity to support children's growth and development. This activity aims to improve the knowledge and skills of Posyandu cadres and parents in stimulating, detecting, and intervening early in the growth and development of children under five. The implementation method includes counseling on the concept and importance of SDIDTK, demonstration of implementation techniques, and direct practicum by participants. Participants were given the opportunity to try the practice of SDIDTK directly with the assistance of the facilitator. Partners in this activity are all parents who have 15 toddlers and 5 Posyandu cadres in East Penfui Village, Central Kupang District, Kupang Regency. Evaluation was carried out through observation of participant involvement, questions and answers, and assessment of practical skills. The results of the evaluation showed that participants participated in the activity enthusiastically, were able to master the steps of SDIDTK well, and understood the importance of an active role in monitoring children's growth and development.